Teologi Religium Merupakan Sarana Perjumpaan Antar Agama-Agama Di Era Modern - Alfri Tandi (Institut Agama Kristen Negeri Kupang, 2021)
Indonesia is a country consisting of various ethnic groups, races, cultures, and religions. Indonesia is a pluralistic country, especially in terms of religion. In which there are six religions legitimized by the state, including Catholic Christianity, Protestant Christianity, Islam, Hinduism, Buddhism and Confucianism. However, there are still many tribal religions that are lived by the Indonesian people, especially in remote areas. Then not infrequently problems arise because of differences of opinion or views from within each religion. This diversity of views triggers inter-religious conflicts ranging from verbal arguments/arguments, mutual suspicion, motions of disapproval of other religions arise, even to divisions and bloodshed (this is a reality that happened in the past and is still visible today). In the problems faced by religions, religious theology is moved and is present to offer to solve the problems faced by religions in order to create peace and harmony on this earth. Religious theology stands alone and starts from facts and truths that are human in nature. Seeing religious pluralism, religious theology invites every religious community to respond to the reality of religious pluralism by means of dialogue that is full of humility and openness between religions.